KESIAPAN PEMBELAJARAN TATAP MUKA PADA ANAK USIA DINI DI TK LIYA III SURABAYA - Aisyah, Aisyah; Insani, Aulia (Universitas PGRI Adi Buana Surabaya, 2022)
Parents and teachers must be able to prepare their children to study at school in accordance with established regulations, namely following the health protocols recommended by the government. The purpose of this community service is to solve problems for PAUD teachers and parents of students in preparing face-to-face learning preparations. This activity was carried out at LIYA III Kindergarten in Surabaya. The method used by the workshop is. The presenters gave various explanations about the preparations that must be made to carry out face-to-face learning for early childhood so that they feel happy and comfortable learning at school. Through this activity, PAUD teachers gain knowledge and skills in preparing children for face-to-face learning in early childhood. The material provided explains various systems for preparing and motivating early childhood in face-to-face learning at school.